Familjeliv: Member Threads – Parents - Språkbanken Text (University of Gothenburg, 2024)
Material from the Familjeliv internet forum.

Material från diskussionsforumet Familjeliv.
Familjeliv: Medlemstrådar – Föräldrar
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik